2020
DOI: 10.3389/fpsyg.2020.01276
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Vagus Nerve Stimulation (tVNS) Improves High-Confidence Recognition Memory but Not Emotional Word Processing

Abstract: Previous clinical research found that invasive vagus nerve stimulation (VNS) enhanced word recognition memory in epileptic patients, an effect assumed to be related to the activation of brainstem arousal systems. In this study, we applied non-invasive transcutaneous auricular VNS (tVNS) to replicate and extend the previous work. Using a single-blind, randomized, between-subject design, 60 healthy volunteers received active or sham stimulation during a lexical decision task, in which emotional and neutral stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 124 publications
3
40
1
3
Order By: Relevance
“…Our study could not confirm the positive findings that resulted from post hoc analyses in two previous studies suggesting that taVNS increases sAA (Ventura-Bort et al, 2018;Warren et al, 2018). Instead, the lack of a significant effect of taVNS on sAA converges with previous zero findings (Giraudier et al, 2020;Koenig et al, 2019). A caveat, however, is that most studies (including the present one) collected stimulated saliva using cotton sponges.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study could not confirm the positive findings that resulted from post hoc analyses in two previous studies suggesting that taVNS increases sAA (Ventura-Bort et al, 2018;Warren et al, 2018). Instead, the lack of a significant effect of taVNS on sAA converges with previous zero findings (Giraudier et al, 2020;Koenig et al, 2019). A caveat, however, is that most studies (including the present one) collected stimulated saliva using cotton sponges.…”
Section: Discussioncontrasting
confidence: 99%
“…Predominantly, these studies are characterized by short stimulation periods, addressing the immediate effects. Psychological targets have been broad (though not all of them are sensitive to tVNS), including: experimentally induced worry (Burger et al, 2019a ); post-error slowing (Sellaro et al, 2015b ); attention to fearful faces (Verkuil and Burger, 2019 ); associative memory (Jacobs et al, 2015 ) or single-item word memory (Giraudier et al, 2020 ; Mertens et al, 2020 ); extinction of fear responses or fear conditioning (Burger et al, 2016 , 2017 , 2018 , 2019b ; Genheimer et al, 2017 ; Szeska et al, 2020 ); implicit spiritual self-representations (Finisguerra et al, 2019 ); flow experience (Colzato et al, 2018b ); response selection during sequential action (Jongkees et al, 2018 ) or during action cascading processes (Steenbergen et al, 2015 ); the recognition of emotions in faces or bodies (Colzato et al, 2017 ; Sellaro et al, 2018 ; Koenig et al, 2019 ); divergent thinking (Colzato et al, 2018a ); conflict-triggered adjustment of cognitive control (Fischer et al, 2018 ); auditory selective attention (Rufener et al, 2018 ) or visual selective attention (Ventura-Bort et al, 2018 ); inhibitory control (Beste et al, 2016 ; Borges et al, 2020 ); automatic motor inhibition (Keute et al, 2018 ); cognitive flexibility (Borges et al, 2020 ; Tona et al, 2020 ); prosocial behavior (Sellaro et al, 2015a ) and reward sensitivity (Neuser et al, 2019 ).…”
Section: Modes Of Applicationmentioning
confidence: 99%
“…Some showed increased sAA levels following tVNS, but not after sham stimulation (Fischer et al, 2018;Ventura-Bort et al, 2018;Warren et al, 2019). Three recent studies did not show any sAA changes in response to tVNS (Koenig et al, 2019;Giraudier et al, 2020;D'Agostini et al under review), Also, documented improvements of sleep quality with tVNS (Bretherton et al, 2019) are inconsistent with LC activation, which is the main brainstem nucleus that promotes arousal.…”
Section: Noradrenergic-related Processes and Markersmentioning
confidence: 99%
“…VNS may induce a state similar to arousal, most likely linked to secretion of noradrenaline and acetylcholine in the brain, neurotransmitters known to mediate attention (Martino et al, 2007;Klinkenberg et al, 2011). Studies have shown that (t)VNS may improve declarative memory retention (Clark et al, 1999;Ghacibeh et al, 2006;Jacobs et al, 2015;Broncel et al, 2020;Giraudier et al, 2020), even in patients with Alzheimer's Disease (Clark et al, 1999;Sjogren et al, 2002;Merrill et al, 2006). Other authors have found mixed results in single-session studies (see Vonck et al, 2014 for review), depending on the stimulation settings (0.5 mA being optimal).…”
Section: Preconscious Impacts On Cognitive Processesmentioning
confidence: 99%